PERAN PEMERINTAH TERHADAP TRANSPARANSI PROGRAM KELUARGA HARAPAN DESA BANUA KECAMATAN BUNGIN - Mirnawati Mirnawati; Monalisa Ibrahim; Abd Razak Useng; Akhyaruddin Hakim (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2021)
This research aims to find out the role of the village government towards the transparency of the family program hopes of Banua Village Bungin District. The population in this study was 110 residents in Banua Village Bungin District of Enrekang Regency, where sampling used is Saturated Sampling using Slovin Formula with the number of Samples 110, this study uses Quantitative Descriptive Methods. Data collection techniques used through Observation, Questionnaire (Angket), Interview, Library Study. Data Analysis techniques used are Descriptive Statistics, Linear Regression, Hypothesis Testing using SPSS 16.0 and Likert Scale. The results of this study showed that the role of the village government towards the transparency of the family program hopes of Banua Village Bungin District with a value of 53% categorized ''influential''. The Indicator of the Role of the Village Government in the form of Provision is Facilities (51%), the Role of the Village Government in the provision of motivation is (54.2%), the Role of the Village Government as a Mediator is (52.8%). While the Transparency Indicator is the Willingness to Access Documents which is (55.4%), Clarity and Completeness of Information that is (54.4%), Open Access is (55.2%), The Regulatory Framework is (49%). So that the role of the village government towards the transparency of the family program hopes Banua Village Bungin Regency with a value of 53% categorized ''influential''.